Determining the age distribution of Colle Gnifetti, Monte Rosa, Swiss Alps, by combining ice cores, ground-penetrating radar and a simple flow model - Konrad, Hannes; Bohleber, Pascal; Wagenbach, Dietmar; Vincent, Christian; Eisen, Olaf (Journal of glaciology, 2013)
Ice cores from cold Alpine glaciers may provide unique paleoclimate information from non-polar latitudes. We explore the three-dimensional internal age distribution of the small cold glacier saddle (Colle Gnifetti, Monte Rosa, Italy/Switzerland) to compare the age/depth relations from four local deep ice cores. Tracking isochronous reflection horizons detected by ground-penetrating radar (GPR) among the core locations reveals consistent dating up to 80 years BP. This approach is confined to recent ages, due to the lack of clear reflections below the firn/ice transition. We attempt to overcome this limitation by including a two-dimensional flow model adapted to the GPR-derived surface accumulation and ice thickness distribution. Modeled and GPR isochrones are compared, indicating agreement in shape but featuring a potential offset of 0-3.5 m. The modeled isochrones are interpolated to the core array with ages assigned according to the ice-core datings. The resulting age distribution is consistent up to 110 years BP, with age uncertainties increasing from 7 to >80 years in the lower half of the ice. This combination of methods is novel for Alpine sites and may be adapted for spatial extrapolation of ice properties other than age.
Elektronische Reproduktion der Druck-Ausgabe
Published online by Cambridge University Press: 10 July 2017
Gesehen am 30.07.2021